Universal hydraulics of the flowering plants: vessel diameter scales with stem length across angiosperm lineages, habits and climates. (22nd May 2014) - Olson, Mark E.; Anfodillo, Tommaso; Rosell, Julieta A.; Petit, Giai; Crivellaro, Alan; Isnard, Sandrine; León‐Gómez, Calixto; Alvarado‐Cárdenas, Leonardo O.; Castorena, Matiss; Enquist, Brian
Abstract Angiosperm hydraulic performance is crucially affected by the diameters of vessels, the water conducting conduits in the wood. Hydraulic optimality models suggest that vessels should widen predictably from stem tip to base, buffering hydrodynamic resistance accruing as stems, and therefore conductive path, increase in length. Data from 257 species (609 samples) show that vessels widen as predicted with distance from the stem apex across angiosperm orders, habits and habitats. Standardising for stem length, vessels are only slightly wider in warm/moist climates and in lianas, showing that, rather than climate or habit, plant size is by far the main driver of global variation in mean vessel diameter. Terminal twig vessels become wider as plant height increases, while vessel density decreases slightly less than expected tip to base. These patterns lead to testable predictions regarding evolutionary strategies allowing plants to minimise carbon costs per unit leaf area even as height increases.